The Effect of the Augmented Reality-Based STAD Model on IPAS Learning Outcomes - Suriyani, Suriyani (Institut of Shanti Bhuana, 2025)
Education in the digital era is undergoing significant transformation with the integration of technology into learning. In the teaching of Natural and Social Sciences (IPAS) at the elementary school level, one of the main challenges is understanding abstract concepts, such as plant parts. To address this challenge, this study examines the effect of applying the Augmented Reality (AR)-based Student Teams Achievement Division (STAD) learning model on students' learning outcomes. The STAD model emphasizes group collaboration in understanding the material, while AR technology enables more realistic interactive visualization. This study employs a quantitative method with a quasi-experimental design. The research subjects consist of 60 fourth-grade students at SDN 03 Bengkayang, divided into an experimental group (STAD with AR) and a control group (conventional method). Data were collected through pretest and posttest assessments as well as observations during the learning process. Data analysis involved normality tests, homogeneity tests, and t-tests. The results indicate a significant difference in learning outcomes between the experimental and control groups. The posttest scores of students in the experimental group were higher than those in the control group, with a more significant improvement after AR-based learning. These findings suggest that integrating the STAD model with AR technology effectively enhances students’ understanding of IPAS material. The findings of this study imply that utilizing digital technology, particularly AR, can serve as an innovative solution for improving the quality of elementary school education. It is expected that this research will serve as a reference for educators in developing technology-based learning methods to enhance student engagement and learning effectiveness.